2019
DOI: 10.1186/s12859-019-2608-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive anticancer drug response prediction based on a simple cell line-drug complex network model

Abstract: BackgroundAccurate prediction of anticancer drug responses in cell lines is a crucial step to accomplish the precision medicine in oncology. Although many popular computational models have been proposed towards this non-trivial issue, there is still room for improving the prediction performance by combining multiple types of genome-wide molecular data.ResultsWe first demonstrated an observation on the CCLE and GDSC datasets, i.e., genetically similar cell lines always exhibit higher response correlations to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…The novelty of our method is in prior clustering of the data (both cell lines and drugs) by utilizing EMD from the theory of optimal mass transport. It has been shown that similar cell lines by their gene expression profiles exhibit similar responses to the (structurally) similar drugs [18,19]. We improved these methods by focusing on the paired cluster of cell line and drugs to which a new pair of cell line-drug in the test set belongs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The novelty of our method is in prior clustering of the data (both cell lines and drugs) by utilizing EMD from the theory of optimal mass transport. It has been shown that similar cell lines by their gene expression profiles exhibit similar responses to the (structurally) similar drugs [18,19]. We improved these methods by focusing on the paired cluster of cell line and drugs to which a new pair of cell line-drug in the test set belongs.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the number of decision trees or selected features make the algorithm computationally expensive; however, it does not improve the performance (prediction) significantly. We also compare our result to the network-based model introduced in [19] (CDCN model) which is the extension of Zhang's dual layer integrated cell line-drug network model [18]. The integrated model does not consider the clustering of the data, but it uses the similarity measure between cell lines and drugs via Pearson correlation.…”
Section: Prediction Of Drug Response In Paired Cell Line-drug Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Chang et al [33] CNN (RF, SVM) SNP 5% leave-out R 2 = 0.843 2018.07.01 Cichonska et al [31] Kernel SNP, MET, EXP, CNV 10-fold CV r = 0.858 2018.09.14 Le et al [19] Network (Kernel) MUT, EXP 5-fold CV r = 0.804 2018.09.14 Juan-Blanco et al [20] Network MUT, EXP LOOCV AUC = ∼0.72 2018.10.10 Yang et al [21] Network + SVM (Kernel) MUT, MET, CNV, PPI 5-fold CV AUC = 0.788 2018.12.07 Liu et al [22] Network EXP 10-fold CV r = 0.73 2019.01. 22 Wei et al [23] Network EXP LOOCV r = 0.63 2019.01. 31 Wang et al [15] EN EXP, PWY 10-fold CV MSE = ∼2.8 2019.01.…”
mentioning
confidence: 99%